Oxidative Status of Marchigiana Beef Enriched in n-3 Fatty Acids and Vitamin E, Treated With a Blend of Oregano and Rosemary Essential Oils - Fusaro, Isa; Cavallini, Damiano; Giammarco, Melania; Manetta, Anna Chiara; Martuscelli, Maria; Mammi, Ludovica Maria Eugenia; Lanzoni, Lydia; Formigoni, Andrea; Vignola, Giorgio (Frontiers in Veterinary Science, 2021)
The aim of this study was to evaluate the effects of basal dietary supplementation with linseed and linseed plus vitamin E in Marchigiana steers young bulls on the instrumental color, oxidative stability and fatty acid composition of beef steaks with and without treatment with a blend of essential oils (oregano and rosemary) after storage times of 0, 3, 6 and 9 days. The fatty acid composition was evaluated in meat after 0 and 9 days of storage. No variation in the fatty acid composition of each type of meat was observed after storage. The use of dietary linseed and vitamin E, compared with linseed alone, significantly improved the oxidative stability, lightness (L*) and redness (a*) of the meat. A higher degree of oxidation was observed in meat samples from animals in the group fed linseed (L) followed by the control group (C) and the group fed linseed and vitamin E (LE). Moreover, the essential oils treatment (O) exert a significant effect on beef oxidative stability of the group LE more than groups C and L during storage. The fatty acid composition of the meat was also affected by the diet: levels of healthful fatty acids (PUFA, n-3 PUFA, n-3 LC PUFA and CLA) were higher in meat from the groups that received linseed than the control group. Our results suggest that dietary vitamin E and treatment with essential oils are effective approaches to preserving the oxidative stability of beef cattle receiving a diet enriched in unsaturated fatty acids for up to 9 days of storage.